G. Stickley’s Magazine “Craftsman”: American Art Criticism on the Abramtsevo and Talashkino Art Groups - Kulinicheva, Ekaterina A. (Actual Problems of Theory and History of Art, 2013)
The Craftsman magazine, founded by а famous American architect Gustav Stickley, from the beginning paid attention to Russia, its life, culture and art. As the magazine upheld ideological principles of Arts and Crafts Movement, the main interest of its authors was the Russian peasantry — and as a result, the folk art and main centers of its revival and promotion — art groups in Abramtsevо and Talashkino. We can say that American art critics assessed the artistic achievements and noted the identity of the art groups, but also introduced them and the national-romantic trend in Russian decorative art in general in terms of the international Arts and Crafts Movement.
Keywords: The Craftsman magazine; Gustav Stickley; Arts and Crafts Movement; Russian decorative art; Abramtsevо; Talashkino